Study the Genesis of Saturn Rings and their Physical Properties - Mahdi, Farid (Iraqi Journal of Science, 2025)
A computer program has been created to calculate the Roche Limit of the rings and satellites of Saturn, showing that many of the rings of the planet are located outside the Roche Limit and still intact and do not accumulate and clump since ancient times, and that many of Saturn satellites are located within the Roche Limit and have not been influenced and crumbled by the tidal forces of the planet. The change of the rings width was studied as a relative function of the mass with the distance from the planet, and the satellite diameters change as a relative function of the mass with the distance from the planet. The results were compared with the condition of the planets and the sun showing almost similar change in the two cases, which induces to conclude that most of Saturn satellites were originally rings moving around the planet and these rings are old and among the raw material of the planet since its inception and not the remains of the satellite destroyed by collision or influenced by the tidal forces when by passing the Roche Limit. The tidal gravitational interaction is not only the most powerful and influential in determining the shape, condition and orbit of the satellite.